Peningkatan Mutu Pendidikan : KEREN Volume 11 di Desa Lambanan, Kecamatan Latimojong, Kabupaten Luwu - Nirwana Halide (RUANG KOMUNITAS: Jurnal Pengabdian Masyarakat, 2023)
This article discusses a social education movement called Kemah Relawan Pendidikan (KEREN), which aims to improve education in remote and mountainous areas of Luwu Regency, particularly in the South Sulawesi and Southeast Sulawesi provinces. KEREN is carried out by a group of volunteers from several volunteer organizations in the region. The movement is implemented without a permanent leadership and guided by field coordinators in every activity. This article focuses on KEREN Volume 11, which took place on February 24th, 25th, and 26th, 2023, in Lambanan Village, Latimojong District, Luwu Regency, South sulawesi province. The research method used is a descriptive qualitative method with field research and primary data obtained from interviews with KEREN volunteers and secondary data obtained from documentation. The article discusses the preparation and implementation of KEREN Volume 11 and the positive impact it has produced. KEREN is expected to help remote communities obtain equal and decent access to education and to promote education in Indonesia.